Shooting psychiatry. Dalla psicoanalisi al DSM-5: come è stata uccisa la psichiatria in America - Brandizzi, Martina; Anzilotti, Carlo (Il sogno della farfalla, 2013)
In concomitance with the release of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders the authors reflect on the causes of the identity crisis that has affected psychiatry over the last decades. This crisis has been brought to light by a number of dramatic events, such as the umpteenth massacre which occurred in into a primary school at Newtown, Connecticut on the 14th December 2011. The event fuelled the debate over the question of an uncontrolled presence of firearms in the country, but this time there was a novelty: the author of the massacre, Adam Lanza, was mentally ill and had never received the necessary treatments. What emerged, therefore, is the dramatic level of decline of the mental health services in the US. This deterioration highlights, as well, the problem of training. Very few doctors choose to specialize in Psychiatry and psychiatric training is based almost exclusively on the DSM whilst the study of classic psychopathology is offered only in few places. This article recounts the history of American psychiatry of the last century, from the arrival of the psychoanalytical doctrine, through to the publication of the first version of the DSM (DSM-I) and the release of the DSM-III, up to the present day. The study of mental health has focused more and more on operationalization, and shunned a more deeper understanding of the phenomenon, whilst European psychopathology of the early 1900s has been abandoned. The authors are in favour of a return to the study of psychopathological profiles, accompanied by a research into the causes of mental health which cannot be separated from considerations of the nonconscious reality of human beings.